2022
DOI: 10.1186/s40814-022-01153-6
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Rehabilitation for Concussion Recovery (i-RECOveR): protocol of an investigator-blinded, randomised, case series with multiple baseline design to evaluate the feasibility and preliminary efficacy of a 12-week treatment for persistent post-concussion symptoms

Abstract: Background Up to 25% of concussed individuals experience persistent post-concussion symptoms (PPCSs) which may interfere with the return to pre-injury activities and cause significant stress. Given that multiple etiological factors are thought to contribute to PPCSs, an interdisciplinary approach is recommended. This pilot study aims to primarily investigate the feasibility of a novel interdisciplinary treatment for PPCSs. Given this intervention is novel, uncertainty exists in terms of potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 127 publications
0
3
0
Order By: Relevance
“…Many of the non-drug interventions described above have been combined into multi-disciplinary programs [29][30][31][32][33][34][35][36]. A 2-year randomized controlled trial with a multidomain lifestyle intervention showed a reduction in cognitive decline based on results of comprehensive neurological testing [37,38].…”
Section: The Importance Of Multimodal Interventionsmentioning
confidence: 99%
“…Many of the non-drug interventions described above have been combined into multi-disciplinary programs [29][30][31][32][33][34][35][36]. A 2-year randomized controlled trial with a multidomain lifestyle intervention showed a reduction in cognitive decline based on results of comprehensive neurological testing [37,38].…”
Section: The Importance Of Multimodal Interventionsmentioning
confidence: 99%
“…While TBI is well known to cause cognitive, motor, and behavioral symptoms, both acutely and as long-term complications, its morbidity is difficult to quantify. Although most TBI is characterized as mild, even these less severe head injuries can bring long-term sequelae [2]. Understanding the severity of TBI and establishing proper diagnostic methods for TBI is critical for the patient's functional recovery and for structuring a personalized rehabilitation plan [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Although most TBI is characterized as mild, even these less severe head injuries can bring long-term sequelae [2]. Understanding the severity of TBI and establishing proper diagnostic methods for TBI is critical for the patient's functional recovery and for structuring a personalized rehabilitation plan [1,2]. Traumatic axonal injury (TAI) comes with high variability in type and degree of neurological impairment, with injury location a significant determinant of prognosis [3].…”
Section: Introductionmentioning
confidence: 99%